Amino Acid Profiling of Zinc Resistant Prostate Cancer Cell Lines: Associations With Cancer Progression. Issue 6 (19th January 2017) - Kratochvilova, Monika; Raudenska, Martina; Heger, Zbynek; Richtera, Lukas; Cernei, Natalia; Adam, Vojtech; Babula, Petr; Novakova, Marie; Masarik, Michal; Gumulec, Jaromir
Abstract : BACKGROUND: Failure in intracellular zinc accumulation is a key process in prostate carcinogenesis. Nevertheless, epidemiological studies of zinc administration have provided contradicting results. In order to examine the impact of the artificial intracellular increase of zinc(II) ions on prostate cancer metabolism, PNT1A, 22Rv1, and PC‐3 prostatic cell lines—depicting different stages of cancer progression—and their zinc‐resistant counterparts were used. To determine "benign" and "malignant" metabolic profiles, amino acid patterns, gene expression, and antioxidant capacity of these cell lines were assessed. METHODS: Amino acid profiles were examined using an ion‐exchange liquid chromatography. Intracellular zinc content was measured by atomic absorption spectrometry. Metallothionein was quantified using differential pulse voltammetry. The content of reduced glutathione was determined using high performance liquid chromatography coupled with an electrochemical detector. Cellular antioxidant capacity was determined by the ABTS test and gene expression analysis was performed by qRT‐PCR. RESULTS AND CONCLUSIONS: Long‐term zinc treatment was shown to reroute cell metabolism from benign to more malignant type. Long‐term application of high concentration of zinc(II) significantly enhanced cisplatin resistance, invasiveness, cellular antioxidant capacity, synthesis of glutathione, and expression of treatment resistance‐ and stemness‐associated genes ( SOX2, POU5F1, BIRC5 ). Tumorous cell lines universally displayed high accumulation of aspartate and sarcosine and depletion of essential amino acids. Increased aspartate/threonine, aspartate/methionine, and sarcosine/serine ratios were associated with cancer phenotype with high levels of sensitivity and specificity. Prostate 77: 604–616, 2017 . © 2017 Wiley Periodicals, Inc.